2007
DOI: 10.1016/j.physbeh.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and hypothalamic effects of a high-protein/low-carbohydrate diet

Abstract: Diets high in fat or protein and extremely low in carbohydrate are frequently reported to result in weight loss in humans. We previously reported that rats maintained on a low carbohydrate-high fat diet (LC-HF) consumed similar kcals/day as chow (CH)-fed rats and did not differ in body weight after 7 weeks. LC-HF rats had a 45% decrease in POMC expression in the ARC, decreased plasma insulin, and increased plasma leptin and ghrelin. In the present study we assessed the effects of a low carbohydrate-high protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…In contrast, the maintenance requirement of protein for omnivores varies from approximately 5% of ME for the rat (NRC, 1995) to 8% of ME for the dog (NRC, 2006). It has been shown that both weight gain and energy intake are decreased in rats consuming a HP diet (Kinzig et al, 2007). In obese cats, the effect of ad libitum consumption of HP diets on energy balance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the maintenance requirement of protein for omnivores varies from approximately 5% of ME for the rat (NRC, 1995) to 8% of ME for the dog (NRC, 2006). It has been shown that both weight gain and energy intake are decreased in rats consuming a HP diet (Kinzig et al, 2007). In obese cats, the effect of ad libitum consumption of HP diets on energy balance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with adults (both with animals and humans) have suggested that high protein diets, combined with physical training, result in lower body fat and higher fat-free mass (18,19). Studies have indicated that, among the benefits of this kind of diet, a reduction in liver lipogenesis may be observed (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with adults (both with animals and humans) have suggested that high protein diets, combined with physical training, result in lower body fat and higher fat-free mass (18,19). Studies have indicated that, among the benefits of this kind of diet, a reduction in liver lipogenesis may be observed (18,20). We can speculate that the growing condition of the animals modifies amino acid metabolism, allowing a deviation of the carbon skeleton from the excessive amino acids to glucose and fatty acids synthesis, favoring lipogenesis (21).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the fact that ghrelin failed to induce body-weight gain in adrenoreceptor (β 1 , β 2 and β 3 ) -knockout mice [325]. It also worth noting that a study by Kinzig et al showed that elevated ghrelin levels were accompanied by increased pro-opiomelanocortin (POMC) expression [326]; and central POMC gene delivery results in decreased food intake and attenuated weight gain in obese Zucker rats [327].…”
Section: Ghrelinmentioning
confidence: 89%